TEACHERS’ PROFESSIONAL ACTIVITY TRAINING IN TERMS OF SUBJECT-ORIENTED EDUCATIONAL PROGRAMME FOR SENIOR SCHOOLCHILDREN - Любягина, Ольга Анатольевна; Гильмеева, Римма Хамидовна (Bulletin of the Chuvash State Pedagogical University named after I Y Yakovlev, 2021)
В настоящее время профильное обучение является неотъемлемой частью системы образования в Российской Федерации. Институциональной формой реализации этой цели выступают профильные школы и профильные классы, в которых за счет изменений в структуре, содержании и организации образовательного процесса в значительной мере учитываются интересы, склонности и способности учащихся. Для организации обучения и достижения профессионального самоопределения старшеклассников в соответствии с их профессиональными интересами и намерениями необходима специальная подготовка педагогов. В статье обобщены особенности профильного обучения старшеклассников и соответствующие им характеристики профессиональной деятельности педагогов. С целью расширения спектра компетенций педагогов, работающих в условиях профильного обучения, предлагается программа повышения квалификации «Вектор профессионального развития» и рассматриваются составляющие ее модули. Особое внимание в программе уделяется направленности на организацию психолого-педагогического сопровождения процесса профессионального самоопределения старшеклассников, свидетельствующего о продуктивности профильного обучения. Апробация представленной программы повышения квалификации подтвердила ее практическую значимость в профессиональной деятельности педагогов в условиях профильного обучения. Статья предназначена директорам и педагогам школ с профильным обучением, работникам системы дополнительного образования, исследователям. Nowadays, subject-oriented education is an integral part of the education system in the Russian Federation. Subject-oriented schools and classes serve as an institutional form of the implementation of this purpose. Due to the changes in structure, content and organization of educational process students’ interests, talents and abilities are to a greater extent considered. Teachers’ special training is needed to promote senior schoolchildren’s decision-making process in terms of choosing their future careers according to their professional interests and intentions. The article provides the features of subject-oriented education of senior schoolchildren and corresponding features of teachers’ professional activity. To enhance the range of teachers’ competences working in the conditions of subject-oriented education, the authors offer the programme for teachers’ professional development “Vector of Professional Development” and consider its modules. Special attention in the programme is focused on the organization of psychological and pedagogical support of the process of professional self-determination of senior schoolchildren demonstrating the efficiency of subject-oriented education. Practical implementation of the presented programme for teachers’ professional development proved its practical value in teachers’ professional activity in the conditions of subject oriented education. The article is intended to heads and teachers of subject-oriented schools, staff of the system of additional professional education, and researchers.